Optimising technological literacy acquirement to protect privacy and security. Issue 5 (4th April 2022) - Hirschprung, Ron S.; Tayro, Shay; Reznik, Eti
ABSTRACT: In the contemporary digital era, users may take actions which may affect their privacy and security without being aware of the consequences. Knowing the consequences, may be perceived as a higher level of usability, above the basic operational skills. This phenomenon is mainly a direct outcome of the gap between users' knowledge and the complexity of the digital systems. The ability to master those systems is known as technological literacy, which thus is a critical factor to protect privacy and security. However, the process of acquiring technological literacy is costly and not trivial. In this research, we address the problem with a qualitative approach, and introduce a methodology named OTLA (Optimising Technological Literacy Acquirement) to achieve optimality between the cost of the teaching process and its benefits. We conducted an empirical study with n = 320 participants on five technological literacy issues, and showed that optimal solutions to this problem can be found. Thus, OTLA has a significant contribution to protecting users' privacy and security in the digital world.